(untitled) (Journal of Pathology of Nepal, 2025)
Background: Thyroid dysfunction is a common endocrine abnormality globally. In Nepal, socio-environmental factors like iodine deficiency, dietary habits, and limited access to healthcare have exacerbated its prevalence. It is the altered serum thyroid stimulating hormone level with normal or altered thyroid hormones (free tri-iodothyronine and free thyroxine). The present study aimed to find the prevalence of thyroid dysfunction among individuals visiting a diagnostic center in Lalitpur, Nepal. Materials and Methods: This was a descriptive cross-sectional study conducted at the Genesis Diagnostic and Clinic in Lalitpur, Nepal, between July 1, 2022, to December 30, 2024. Ethical clearance was granted by the Ethical Review Board (Reference number: 1384). Patients who had undergone thyroid function tests, like assessments of free tri-iodothyronine, free thyroxine and thyroid-stimulating hormone, were enrolled. Enumeration sampling was done. SPSS version 22 was used for data analysis. Results: Out of 520 patients who underwent thyroid function test, thyroid dysfunction was seen in 118 (22.69%) patients. Among them, 93 (17.88%) had subclinical hypothyroidism, 13 (2.50%) had subclinical hyperthyroidism, six (1.20%) had hypothyroidism, and six (1.20%) had hyperthyroidism. There were 47 (39.84%) males and 71 (60.16%) females with thyroid dysfunction. The male-to-female ratio was 1:1.51. The age range was 20 to 90 years with a mean age of 44.53 ± 14.61 years. The maximum number of thyroid dysfunction cases occurred in the 30-39 years age group. Conclusion: The prevalence of thyroid dysfunction is still higher in our study population and is similar to studies done in similar settings. Subclinical hypothyroidism was the most common thyroid dysfunction with female predominance.